Prevalence and genotype distribution of human papillomavirus in women with cervical cancer or cervical intraepithelial neoplasia in Henan province, central China. Issue 12 (1st March 2020) - Chen, Guanghui; Zheng, Peiming; Gao, Lan; Zhao, Jing; Wang, Ying; Qin, Wangsen
Abstract: To evaluate the prevalence of human papillomavirus (HPV) infection and its genotype among women with cervical lesions in Henan Province, central China. A total of 1317 cervical scrapes from patients with cervical intraepithelial neoplasia 1 (CIN1) (n = 91), CIN2/3 (n = 466), and cervical cancer (CC; n = 760) were collected from 2013 to 2018, and then tested for HPV genotypes using polymerase chain reaction followed by flow‐through hybridization assay. The prevalence of HPV was 62.64% for patients with CIN1, 86.91% for patients with CIN2/3%, and 89.21% for patients with CC. In total, the HPV prevalence was 86.56%, and the most common HPV type was HPV16 (58.77%) followed by HPV58 (10.33%), 18 (7.67%), 52 (6.61%), and 33 (5.54%). In this study, the high‐risk HPV cumulative attribution rate of nine‐valent vaccine coverage was markedly higher than that of bivalent or quadrivalent vaccine coverage in each histopathological category or overall ( P < .001). Single HPV infection was the main infection category in each histopathological diagnosis, and the total infection rate was 65.83% (867/1317; P < .001). The prevalence of HPV16 or single HPV infection increased with the severity of cervical lesions ( P < .001). HPV16, 58, 18, 52, and 33 may be predominant high‐risk factors for cervical lesions in Henan Province. The nine‐valent prophylactic HPV vaccine is more effective than a bivalent or quadrivalent vaccine for protecting women from CC in the region. Highlights: This was the largest study to analyze the prevalence and genotype distribution of HPV in women with cervical lesions in Henan Province. HPV16 was the most common genotype in each histopathological category, and HPV52 and 58 were also relatively prevalent. Single infection rather than multiple infections constituted the main infection category. The prevalence of HPV16 or single infection increased with the severity of cervical lesions.